2009
DOI: 10.3928/01484834-20090828-02
|View full text |Cite
|
Sign up to set email alerts
|

Looking Is Not Seeing: Using Art to Improve Observational Skills

Abstract: This project evaluated the effects of an art museum experience on the observational skills of nursing students. Half of a class of non-nurse college graduates entering an accelerated master's degree program (n = 34) were assigned to a museum experience, whereas the other half (n = 32) received traditional teaching methods. Using original works of art, students participated in focused observational experiences to visually itemize everything noted in the art piece, discriminate visual qualities, recognize patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 23 publications
1
56
0
Order By: Relevance
“…The data were analyzed using univariate statistics followed by Wilcoxon Mann-Whitley U tests and t tests. The results indicated that on five out of the six photographs, students who participated in the museum activity were able to identify more signs and symptoms, list more objective clinical data, and were able to offer more alternative diagnoses when performing a differential diagnosis with a clinical picture than students who received the traditional clinical teaching (p < 0.05) (Pellico et al 2009). …”
Section: Spiritualitymentioning
confidence: 88%
See 1 more Smart Citation
“…The data were analyzed using univariate statistics followed by Wilcoxon Mann-Whitley U tests and t tests. The results indicated that on five out of the six photographs, students who participated in the museum activity were able to identify more signs and symptoms, list more objective clinical data, and were able to offer more alternative diagnoses when performing a differential diagnosis with a clinical picture than students who received the traditional clinical teaching (p < 0.05) (Pellico et al 2009). …”
Section: Spiritualitymentioning
confidence: 88%
“…The most recent study was conducted with non-nurse college graduate students (n = 66) enrolled in an accelerated master's degree nursing program (Pellico et al 2009). Students in a medical-surgical baccalaureate nursing course were divided into 12 clinical groups.…”
Section: Spiritualitymentioning
confidence: 99%
“…In Yale University, when a group of Medical Students, which was observed that they always miss the details that verifies the diagnosis, were given art lecture at the museum over authentic works of art, it is observed that the ability of the group to observe and identify was improved considering another group who didn't get that lecture (Braverman, 2001). According to another research based on the understanding of "Looking is not seeing", lectures were also given to nursery students at art museums in order to improve their observation abilities (Pellico, Friedlaender & Fennie, 2009). There are researches, with medical students whom there was concern that their physical examination skills are diminishing, where there are meaningful results that studies of careful examination and observation of art works also improves seeing skills.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be beneficial to explore the additional benefits of artistic approaches beyond anatomy learning. For example, the observational skills that are developed through the use of artistic methods can also be transferable to clinical practice (Bardes, Gillers, & Herman, 2001;Boudreau, Cassell, & Fuks, 2008;Jasani & Saks, 2013;Kirklin, Duncan, McBride, Hunt, & Griffin, 2007; Naghshineh et al, 2008;Pellico et al, 2009). In order to implement a novel or innovative method into your curriculum, it may be necessary to convince others of the value of your approach.…”
mentioning
confidence: 99%
“…The pedagogical value of artistic methods are primarily related to the motor skills and cognitive processes that are engaged when using such approaches. Research evidence suggests that key elements of observation (Backhouse, Fitzpatrick, Hutchinson, Thandi, & Keenan, 2017;Chamberlain et al, 2014;Jasani & Saks, 2013;Lyon, Letschka, Ainsworth, & Haq, 2013;Moore, Lowe, Lawrence, & Borchers, 2011;Pellico, Friedlaender, & Fennie, 2009) reflection and repetition (Backhouse et al, 2017;Lyon et al, 2013), and visualisation (Pandey & Zimitat, 2007) should be incorporated and emphasised within any artistic learning approach. Haptic (Jones, Minogue, Tretter, Negishi, & Taylor, 2006;Woods & Newell, 2004) and visuospatial abilities (Garg, Norman, & Sperotable, 2001;Nguyen, Mulla, Nelson, & Wilson, 2014;Nguyen, Nelson, & Wilson, 2012) should also be considered.…”
mentioning
confidence: 99%